2015
DOI: 10.4037/nci.0000000000000110
|View full text |Cite
|
Sign up to set email alerts
|

Home Monitoring for Cardiovascular Implantable Electronic Devices

Abstract: Recent technological advances in the management of patients with cardiovascular implantable electronic devices (CIEDs) have expanded clinicians’ ability to remotely monitor patients with CIEDs. Remote monitoring, in addition to periodic in-person device evaluation, provides many advantages to patients and clinicians. Aside from the therapeutic and diagnostic benefits of pacemakers, implantable cardioverter-defibrillators, cardiac resynchronization therapy devices, and implantable loop recorders, improvement in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 31 publications
0
1
0
2
Order By: Relevance
“…Although several studies indicated electronic data collection as a convenient way of implementing a continuous follow-up in regular time [ 34 , 35 ], especially in electronic devices for home monitoring [ 36 , 37 ], the follow-up timepoint is dynamic and unbalanced in patients with adenomyosis and menstrual disorders, especially after treatment, such as gonadotropin-releasing hormone (GnRH) cessation of menstruation to-be-decided [ 33 ]. To pinpoint the date of each menstrual period to monitor the patient’s symptom burden, a flexible schedule must be developed in advance, especially to establish the trigger event so the platform can send follow-up information to patients, which poses a challenge to the available technology of the follow-up system.…”
Section: Discussionmentioning
confidence: 99%
“…Although several studies indicated electronic data collection as a convenient way of implementing a continuous follow-up in regular time [ 34 , 35 ], especially in electronic devices for home monitoring [ 36 , 37 ], the follow-up timepoint is dynamic and unbalanced in patients with adenomyosis and menstrual disorders, especially after treatment, such as gonadotropin-releasing hormone (GnRH) cessation of menstruation to-be-decided [ 33 ]. To pinpoint the date of each menstrual period to monitor the patient’s symptom burden, a flexible schedule must be developed in advance, especially to establish the trigger event so the platform can send follow-up information to patients, which poses a challenge to the available technology of the follow-up system.…”
Section: Discussionmentioning
confidence: 99%
“…«Forsking viser at pacemakerpasientar med telemonitorering har større overlevingsrate enn dei som ikkje har det.» Legen og sjukepleiaren vil som regel velje å inkludere pasienten i TM-systemet under opphaldet etter implantasjonen, og i alle fall helst i løpet av 14 dagar (2). Feil på PM og leidningar, eller arytmiar, løyser ut alarmar (2,15). Dersom det oppstår alarmar som fører til oppmøteevaluering, er det sannsynleg at det blir sett i verk tiltak innanfor programmering eller medikamentell behandling som kan føre til betre resultat (3).…”
Section: Bruk Av Telemonitoreringunclassified
“…TM har vist seg å gjere pasientane meir tilfredse enn tradisjonelle kontrollar (2). Svaert mange av dei som får pacemaker, er eldre menneske, og helsepersonell må vere bevisste på korleis dei introduserer TM for denne gruppa.…”
Section: Meir Tilfredse Pasientarunclassified